Motivational Interviewing for Loved Ones in Early Psychosis: Development and Pilot Feasibility Trial of a Brief Psychoeducational Intervention for Caregivers - Kline, Emily R.; Thibeau, Heather; Sanders, Aliyah S.; English, Kelly; Davis, Beshaun J.; Fenley, Alicia R.; Keshavan, Matcheri S. (Frontiers in Psychiatry, 2021)
Treatment delay and non-adherence in first episode psychosis is a pressing public health problem. Ambivalence regarding psychiatric intervention and labeling among young people with psychosis is a contributing factor. For these individuals, caregivers often facilitate the pathway to care and support ongoing engagement and adherence. Caregivers describe distress and burden associated with this role. This manuscript describes the development and pilot feasibility testing of a motivational interviewing-derived communication training for caregivers of individuals with untreated or under-treated early course psychosis. Individuals with lived experience were consulted in the intervention development process. The training consisted of four sixty-minute sessions teaching the philosophy and basic skills of motivational interviewing as well as two brief practice calls. Feasibility was assessed with regard to study enrollment, retention, and completion. Satisfaction was assessed through the Client Satisfaction Questionnaire and qualitative feedback. Thirty-one caregivers consented to this pilot feasibility trial and participated via telehealth over the course of five months. Intervention completion and reported satisfaction were high, with 94% of consented participants completing at least three training sessions and 84% reporting that they would “definitely” recommend the training to a friend in similar circumstances. There were no between-clinician differences in MILO session attendance (F [2] = 0.53, p = .596) or satisfaction total scores (F [2] = 1.03, p = .371). Brief motivational interviewing skills training appears to be a feasible and valued intervention for caregivers of individuals with poorly managed early course psychosis.